Branding Development and Financial Recording Assistance at Barokah Grocery Stalls - Purwaning Astuti, Ismadiyanti; Amira, Sophia Myska (Jurnal Abdimas Ekonomi dan Bisnis, 2026)
Grocery stores in Indonesia are proliferating, with an increase reaching approximately 2.5 million units. This development makes grocery stores important to the general economy and community life. Grocery stores are one part of the MSMEs that sell products for daily needs. One grocery store in the Colomadu district is Warung Kelontong Barokah. The problem faced by the Barokah grocery store is that it has not yet branded its business and has not yet recorded financial transactions for sales and purchases that have been made. The purpose of this community service activity is to increase the income and profits of the grocery store through branding development and assistance with digital and straightforward financial recording through a mobile application. The method used is mentoring and training. This activity can increase understanding of the importance of branding for businesses and financial recording, with support from the community service team. Implementing business branding through banners can increase product sales from Warung Kelontong Barokah, so that turnover or sales increase. In addition, digital financial record keeping assistance is provided using the Buku Warung application to track the shop's income and expenses. Good financial record keeping is crucial for understanding the business's financial condition and profitability. Branding activities and digital financial record keeping training can increase sales turnover.